Breast cancer profiles of women presenting with newly diagnosed breast cancer at Universitas Hospital (Bloemfontein, South Africa) - Puleng R. Matatiele; Wilhelmina M.J. van den Heever (South African Family Practice)
Profiles of 56 women presenting with breast cancer at Universitas Hospital, Bloemfontein was compiled using a structured questionnaire. Most were older than 50 years, white, were multiparous (92%) and had their first full-term pregnancy before 21 years. The small group of young women comprised mainly of Black women.